Development and validation of a conceptual test for the human circulatory system - Emerson Gaylan; Suzette Elladora; John Kenneth Taneo; Collenn Callanga; Manilyn Piloton-Narca; Jonavie Becbec; Joje Mar P Sanchez (University of Muhammadiyah Malang, 2024)
Current biology assessments often lack a strong emphasis on conceptual understanding, which may limit students' ability to apply knowledge in real-world contexts. This study aimed to develop and validate a concept test to assess high school student's understanding of the human circulatory system. The test was carefully designed using the revised Bloom's Taxonomy and aligned with the K-12 curriculum. Initial content validation by biology education experts ensured accuracy and relevance, leading to refinements in the test items. Item quality was enhanced through dichotomous Rasch analysis following preliminary testing with 100 students. After a second administration to a new group of 100 students, further analysis confirmed the test's reliability and validity. A final round of testing with an additional 100 students yielded a Cronbach's alpha of 0.79, confirming internal consistency. The study concluded that the developed concept test is valid and reliable for assessing students' understanding of the circulatory system, providing teachers with a tool to refine instructional methods. Future recommendations involve expanding and updating test items to ensure relevance, integrating technology-enhanced questions to improve the assessment of student comprehension, and evaluating reliability across diverse contexts.